Natural fibre reinforced biodegradable polymer composites. - Salit, Mohd Sapuan; Japar, Sahari (2012)
Currently, numerous research groups have explored the production and properties of biocomposites where the polymer matrices are derived from renewable resources such as poly lactide (PLA), thermoplastic starch (TPS), cellulose and polyhydroxyalkanoates (PHAs). This review is carried out to evaluate the development and properties of natural fibre reinforced biodegradable polymer composites. They are the materials that have the capability to fully degrade and compatible with the environment.